Colletteichthys flavipinnis, a new toadfish species from Sri Lanka and India (Teleostei: Batrachoididae) - Greenfield, David W.; Bineesh, K. K.; Akhilesh, K. V. (Zootaxa, 2012)
The third known species in the genus Colletteichthys is described from Sri Lanka and India. Colletteichthys flavipinnisdiffers from C. dussumieri in having one instead of two or more tentacles above the eye. It differs from both C. occidentalisand C. dussumieri in having yellow-orange fins, and from C. occidentalis in usually having 16 instead of 15 anal-fin raysand 20 instead of 19 dorsal-fin rays, and in having a slightly smaller ( 1–2% SL) eye. Mitochondrial COI barcode interspecific distance is 4.4% between C. flavippinis and C. dussumieri.